2022
DOI: 10.3389/fcvm.2022.798639
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PTEN Promotes Autophagy via Concurrent Reduction in Apoptosis in Cardiac Hypertrophy in PPAR α−/− Mice

Abstract: Cardiac hypertrophy is characterized by an increase in the size of the cardiomyocytes which is initially triggered as an adaptive response but ultimately becomes maladaptive with chronic exposure to different hypertrophic stimuli. Prolonged cardiac hypertrophy is often associated with mitochondrial dysfunctions and cardiomyocyte cell death. Peroxisome proliferator activated receptor alpha (PPAR α), which is critical for mitochondrial biogenesis and fatty acid oxidation, is down regulated in hypertrophied cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…In arrhythmia, AKAP150 acts in two ways: it intensifies arrhythmia caused by calcium channel-related gene mutation [13], and it may have a therapeutic effect on arrhythmia caused by potassium channel-related gene mutation [14,15]. β1-adrenergic receptor (β-AR) stimulation in vitro and in vivo increased the expression and activity of matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9) in cardiac myocytes [16]; it also induced cardiomyocyte apoptosis [7,17,18]. In addition, β1-AR-mediated increase in cyclic adenosine monophosphate was greater in AKAP5 null myocytes [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In arrhythmia, AKAP150 acts in two ways: it intensifies arrhythmia caused by calcium channel-related gene mutation [13], and it may have a therapeutic effect on arrhythmia caused by potassium channel-related gene mutation [14,15]. β1-adrenergic receptor (β-AR) stimulation in vitro and in vivo increased the expression and activity of matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9) in cardiac myocytes [16]; it also induced cardiomyocyte apoptosis [7,17,18]. In addition, β1-AR-mediated increase in cyclic adenosine monophosphate was greater in AKAP5 null myocytes [19].…”
Section: Introductionmentioning
confidence: 99%
“…β 1-adrenergic receptor ( β -AR) stimulation in vitro and in vivo increased the expression and activity of matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9) in cardiac myocytes [ 16 ]; it also induced cardiomyocyte apoptosis [ 7 , 17 , 18 ]. In addition, β 1-AR–mediated increase in cyclic adenosine monophosphate was greater in AKAP5 null myocytes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the down-regulated genes were enriched in the cholesterol metabolism, in uenza A, measles and NOD-like receptor signaling pathway, among which NOD-like receptor signaling has a role in regulating autophagy 12 . As for the 0.4 mg/mL matrine treated group, we found that, compared with the control group, the up-regulated DEGs are enriched in signal transduction, including adrenergic signaling in cardiomyocytes 13,14 , Hippo signaling pathway 15,16 , Apelin signaling pathway 17 and calcium signaling pathway 18,19 , and these are closely related to autophagy. The down-regulated genes were also enriched in signal transduction, including the NOD-like receptor signaling pathway, Il-17 signaling pathway, AGE-RAGE signaling pathway in diabetic complications, and Chemokine and JAK-STAT signaling pathways, among which the NOD-like receptor signaling pathway, IL-17 signaling pathway 20 , AGE-RAGE signaling pathway 21 and JAK-STAT signaling pathway 22 regulate autophagy (Fig.…”
Section: Analysis Of the Differently Expressed Genes (Degs)mentioning
confidence: 82%
“…It has been demonstrated that all of these signaling pathways are important in the process of autophagy 33,34 . Alterations in the signals, will drive autophagy-related diseases such as heart disease 13 , neurodegenerative diseases 19 and cancer 15,17 . Furthermore, most of the above signaling pathways are important in the development of PKDs.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen treatment resulted in a partial increase in ERα expression, which may be attributed to the stabilization of inactivated cytoplasmic ERα [ 53 , 54 ]. Moreover, all three compounds led to the cleavage of PARP (116 kDa) and the formation of an 89-kDA PARP fragment, which is a key marker of apoptotic cell death [ 55 57 ]. The effect grew with the increase of the compound concentration from 5 to 15 µM.…”
Section: Resultsmentioning
confidence: 99%